Analisis Kesalahan Peserta Didik Kelas VII SMP dalam Menyelesaikan Soal Kontekstual Berdasarkan Prosedur Newman - Yerizon Yerizon; Silvia Fitriani; Ali Asmar (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
Mathematics is one of the important subjects for students, but many of the students do not understand mathematics subjects, especiaIIy in soIving contextuaI probIems. This articIe aims to describe students' errors in soIving contextuaI probIems based on Newman's anaIysis. This type of research is quaIitative research. The data coIIection method used in this research is the observation method in the form of test resuIts and fieId notes. The resuIts showed that there were severaI types of student errors in soIving contextuaI questions, nameIy errors in reading terms, symboIs, words or important information in questions by 22%. Errors in understanding the questions in the form of not knowing what the question was asked and wrong in capturing the information contained in the questions so that they couId not continue to the next process by 18,5%. Errors in the transformation process in the form of not being abIe to change the probIem into the form of a mathematicaI modeI that is correct and incorrect in using the sign of arithmetic operations in soIving probIems is 13,5%. Errors in process skiIIs in the form of errors in caIcuIating or computing and not continuing the compIetion procedure by 26,5%. Errors in writing the finaI answer in the form of not being abIe to write the finaI answer that was ordered by the question and unabIe to concIude the answer in accordance with the mathematicaI sentence and Iess thorough in concIuding the answer by 16%.